Cambodia : Post-Ketsana Disaster Needs Assessment - World Bank (Washington, DC, 2013)
This report was undertaken in the wake of the Ketsana Disaster, to assess damage, losses, and resource requirements for recovery. Typhoon Ketsana hit Cambodia between September 29 and October 5, 2009. Fourteen out of 24 provinces were affected by the storm and subsequent flash floods. The report addresses macro-economic impacts, livelihood and social impacts, disaster risk management requirements, and recovery and reconstruction requirements. The report concludes that the process of data collection and management for assessing damages and losses as well as tracking emergency assistance has to be improved, along with capacity building activities for both the line ministries and national and sub-national Committees for Disaster Relief to facilitate their participation in the recovery process.